Digital Financial Inclusion: Examining The Role of Mobile Technology in Expanding Access to Capital - Alfiana, Alfiana; Putri, Andiena Nindya; Sujai, Muhammad; Amalo, Fitriningsih; Hertina, Dede (Dinasti International Journal of Economics, Finance & Accounting, 2025)
Digital financial inclusion has become a key priority in efforts to reduce economic disparities, particularly among underserved populations by formal financial institutions. This study aims to examine the role of mobile technology in expanding access to capital by reviewing recent literature. Mobile technology offers practical solutions for individuals and small businesses to access financial services, such as microcredit, money transfers, and savings, without relying on traditional banking infrastructure. Furthermore, the adoption of this technology has been shown to accelerate financial inclusion in developing countries, where access to financial services is often constrained by geographical and economic factors. However, this study also highlights emerging challenges, such as low digital literacy, limited network coverage, and data security concerns. The findings provide valuable insights for policymakers, financial service providers, and technology stakeholders to develop more inclusive and sustainable strategies. Thus, mobile technology has significant potential to become a key driver in achieving broader financial inclusion in the future